HAP2(GCS1)-Dependent Gamete Fusion Requires a Positively Charged Carboxy-Terminal Domain - Wong, Julian L.; Leydon, Alexander R.; Johnson, Mark A. (PLOS Genetics, 2010)
HAP2(GCS1) is a deeply conserved sperm protein that is essential for gamete fusion. Here we use complementation assays to define major functional regions of the Arabidopsis thaliana ortholog using HAP2(GCS1) variants with modifications to regions amino(N) and carboxy(C) to its single transmembrane domain. These quantitative in vivo complementation studies show that the N-terminal region tolerates exchange with a closely related sequence, but not with a more distantly related plant sequence. In contrast, a distantly related C-terminus is functional in Arabidopsis, indicating that the primary sequence of the C-terminus is not critical. However, mutations that neutralized the charge of the C-terminus impair HAP2(GCS1)-dependent gamete fusion. Our results provide data identifying the essential functional features of this highly conserved sperm fusion protein. They suggest that the N-terminus functions by interacting with female gamete-expressed proteins and that the positively charged C-terminus may function through electrostatic interactions with the sperm plasma membrane.